2014
DOI: 10.1371/journal.pntd.0003192
|View full text |Cite
|
Sign up to set email alerts
|

Physician Survey to Determine How Dengue Is Diagnosed, Treated and Reported in Puerto Rico

Abstract: Dengue is a major cause of morbidity in Puerto Rico and is well-known to its physicians. Early case identification and timely initiation of treatment for patients with severe dengue can reduce medical complications and mortality. To determine clinical management and reporting practices, and assess knowledge of dengue and its management, a survey was sent to 2,512 physicians with a medical license in Puerto Rico. Of the 2,313 physicians who received the survey, 817 (35%) completed the questionnaire. Of the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 25 publications
3
28
1
1
Order By: Relevance
“…26 Limited recognition of the critical phase of disease by clinicians was also demonstrated in a survey conducted in Puerto Rico. 16 These surveys were conducted in endemic areas and reported higher response rates than our survey. However, it is likely that physicians working in areas which see only sporadic dengue (such as south Texas) have less knowledge about dengue, especially since U.S. medical education often lacks tropical medicine training.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…26 Limited recognition of the critical phase of disease by clinicians was also demonstrated in a survey conducted in Puerto Rico. 16 These surveys were conducted in endemic areas and reported higher response rates than our survey. However, it is likely that physicians working in areas which see only sporadic dengue (such as south Texas) have less knowledge about dengue, especially since U.S. medical education often lacks tropical medicine training.…”
Section: Discussionmentioning
confidence: 51%
“…[12][13][14] Fatality rates for hospitalized patients with severe dengue can be as high as 10%; however, studies have reported that mortality rates can be reduced to < 0.5% with early case identification and timely initiation of correct clinical management. 1,15,16 During May-October 2013, the Mexican state of Tamaulipas, which borders Texas, experienced a dengue epidemic and ∼5,500 suspected dengue cases were reported. 17 During the same period in Texas, 53 laboratory-confirmed dengue cases (median patient age = 28 years, range = 1-85 years) were detected in south Texas border counties; 26 (49%) were locally acquired.…”
Section: Introductionmentioning
confidence: 99%
“…Since clinical manifestations, epidemiology and mosquito vectors of CHIKV overlap with ZIKV and DENV, differential diagnosis would be necessary for patients returning from endemic regions. For example, misdiagnosis of DENV as CHIKV could delay intensive supportive treatment for DENV which may affect the progression to severe disease and fatality almost 10‐fold (Lam et al, ; Mayurasakorn & Suttipun, ; Schilling, Emmerich, Günther, & Schmidt‐Chanasit, ; Tomashek et al, ). Also, severe bleeding in DENV patients could occur upon initiation of arthralgia‐alleviating non‐steroidal anti‐inflammatory drugs prescribed to alleviate CHIKV manifestations (Laoprasopwattana, Kaewjungwad, Jarumanokul, & Geater, ).…”
Section: Discussionmentioning
confidence: 99%
“…We compared a priori selected key indicators of dengue clinical management previously identified as concerns in Puerto Rico 4,17 . Primary outcome measures were defined as the proportion of patients who were not given corticosteroids, prophylactic platelet transfusions, and non-isotonic intravenous saline solutions throughout hospitalization or during the critical phase of dengue (defined as 48 hours after last documented temperature ≥38°C; patients without documented fever during hospitalization were excluded from this analysis).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical management concerns in Puerto Rico included failure to recognize dengue, warning signs for severe disease, or early signs of shock; infrequent patient monitoring; administration of intravenous non-isotonic saline solutions; and widespread use of corticosteroids despite evidence against their use 13-15 . Some of these issues were also identified in a review of fatal dengue cases from 1992–1996 16 and were further investigated by an assessment of physicians’ clinical knowledge and practices in 2007–2008 17 . During the latter assessment, 40% of respondents reported using corticosteroids regularly to treat dengue, and the majority were not familiar with appropriate intravenous fluid usage or indications for platelet or blood transfusion.…”
Section: Introductionmentioning
confidence: 99%